7- The Diaspora and Domestic Insurgencies in Africa - Omeje, Kenneth (African Sociological Review, 2007)
This article engages the emerging discursive reconstruction in the West of the African diaspora, in particular, the debate that the African diaspora plays a prominent role in promoting domestic insurgencies and armed conflicts in their home countries, especially in the post-9/11 dispensation. Based on a taxonomy of the African diaspora vis-à-vis other significant diasporic populations, the article critically explores the views held by many Western Africanists and policy makers about the instrumentality of financial remittances and other logistical support from Africans in the diaspora in the instigation, aggravation and prolongation of political insurgencies and extremist activities in their home states. The author argues that the emerging reconstruction of the image and role of the African diaspora in political conflicts on the continent is essentially a consequence of the post-9/11 re-securitisation of Africa as a zone of error and anger by influential policy makers in theWest.